Estimation and correction of Cerenkov-light on luminescence image of water for carbon-ion therapy dosimetry. (June 2020) - Yabe, Takuya; Akagi, Takashi; Yamamoto, Seiichi
Highlights: Luminescence imaging of water has potential for carbon-ion therapy dosimetry. Luminescence image had some differences from dose distribution due to Cerenkov-light. Measured luminescence image was corrected by subtracting Monte Carlo simulation-based Cerenkov-light. Corrected luminescence image had almost identical distributions to the dose. Abstract: Purpose: The luminescence images of water during the irradiation of carbon-ions provide useful information such as the ranges and the widths of carbon-ion beams. However, measured luminescence images show higher intensities in shallow depths and wider lateral profiles than those of the dose distributions. These differences prevent the luminescence imaging of water from being applied to a quality assurance for carbon-ion therapy. We assumed that the differences were due to the contaminations of Cerenkov-light from the secondary electrons of carbon-ions as well as the prompt gamma photons in the measured image. In this study, we applied a correction method to a luminescence image of water during the irradiation of carbon-ion beams. Methods: We estimated the distribution of the Cerenkov-light in water during the irradiation of carbon-ions by Monte Carlo simulation and subtracted the simulated Cerenkov-light from the depth and lateral profiles of the measured luminescence image for 241.5 MeV/u-carbon-ions. Results: With these corrections, we successfully obtained depth and lateral profiles whose distributions are almost identical to the dose distributions of carbon-ions. The high intensities in the shallow depth areas decreased and the Bragg peak intensity increased. The beam widths of the measured images approached those of the ionization chamber. Conclusions: These results indicate that the luminescence imaging of water with our proposed correction has potential to be used for dose distribution measurements for carbon-ion therapy dosimetry.